A hybrid engine concept for multi-fuel blended wing body. Issue 6 (30th September 2014) - Singh, Riti; Gangoli Rao, Arvind; Yin, Feijia; P. van Buijtenen, Jos
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present a novel hybrid engine concept for a multi-fuel blended wing body (MFBWB) aircraft and assess the performance of this engine concept. Design/methodology/approach – The proposed hybrid engine concept has several novel features which include a contra-rotating fan for implementing boundary layer ingestion, dual combustion chambers using cryogenic fuel (liquefied natural gas [LNG] or liquid hydrogen [LH2]) and kerosene in the inter-turbine burner (in flameless combustion mode) and a cooling system for bleed air cooling utilizing the cryogenic fuel. A zero-dimensional thermodynamic model of the proposed hybrid engine is created using Gas Turbine Simulation Program to parametrically analyse the performance of various possible engine architectures. Furthermore, the chosen engine architecture is optimized at a cycle reference point using a developed in-house thermodynamic engine model coupled with genetic algorithm. Findings – Using LH2 and kerosene, the hybrid engine can theoretically reduce CO2 emissions by around 80 per cent. Using LNG and kerosene, the CO2 emissions are reduced by more than 20 per cent as compared to the baseline engine. Practical implications – The hybrid engine is being investigated in the AHEAD project co-sponsored by the European Commission. This unique aircraft and engine combination will enable aviation to use cryogenic fuels like LH2 or LNG, and will make aviation sustainable. Originality/value – The MFBWB concept and the hybrid engine is a novel concept which has not yet been investigated before. The potential implications of this technology are far reaching and will shape the future development in aviation.